Phase transfer technique for the study of deproteinised natural rubber latex - Tangboriboonrat P; Kuhakarn S; Suchiva K; Tuchinda P (Journal of Natural Rubber Research, 1996)
Phase transfer technique, using benzyldimethylhexadecylammonium chloride as a titrant and toluene as a solvent, was employed for the charecterisation of deproteinised natural rubber latex. Results from critical transfer concentration values and nitrogen contents showed that proteins bound to natural rubber particles were not completely removed by using the enzyme alcalase. Apparently, the remaining proteins might be denatured and, hence, promoted the formation of destabilised and suspended rubber at the toluene/water interphase after phase transfer.
Keywords: Deproteinised natural rubber latex; Phase transfer technique